ARE THE REGIONAL FISCAL INDEPENDENCE, AND REGIONAL POVERTY RATE AS THE FACTOR OF POLITICAL BUDGET CYCLE IN ELECTION YEAR: EVIDENCE IN INDONESIA - Gultom, Maria Maranatha (Journal of Indonesian Applied Economics, 2024)
Purpose This study aims to determine the factors of political budget practices carried out by incumbents ahead of regional elections as an incumbent strategy to demonstrate their competence to voters by politicizing the budget on social and investment spending. Design/methodology/approach In this study, the samples were used in 398 districts in Indonesia that held local elections in 2020, 2018, and 2017. Data analysis was performed by panel data regression analysis using Eviews 10. Findings The researcher found that from the two factors that indicate political budget practices such as the level of regional fiscal independence, and the level of regional poverty, the incumbent regional head has a different strategy for politicizing the government spending. The more higher fiscal independence rate of the region, the incumbents regional head tends to increase spending on investment in machines and equipment. Meanwhile, the more higher the poverty rate of the region, the incumbent regional head will tend to increase social spending. Research limitations/implications This study has limitations; there are still districts/cities whose data is incomplete but included in this sample. This study aims to provide theoretical contributions and empirical evidence for academics, researchers, and readers about the practice of the political budget cycle carried out by regional heads before the election with the aim of politics to be able to win back the next election so that this study was formed with samples of all districts in Indonesia. Originality/value This study uses the regional fiscal independence, and regional poverty rate as independent variables, and all components of capital expenditure as dependent variables that have not been used by previous studies, especially in Indonesia.